Peningkatan Hasil Belajar Siswa dengan Menggunakan Model Problem Based Learning pada Materi Q.S At-Tin - Annisa Ainun Salehah; Nurul Fadhilah; Ghita Fauziah (Indonesian Journal of Islamic Education Studies (INJURIES), 2024)
This study aims to determine the extent to which the improvement of Islamic Religious Education learning outcomes on Q.S At-Tin material by using the Problem Based Learning learning model. The form of this research is class action research (PTK), where the object of the researcher is only centered on the learning process by using the Problem Based Learning learning model and audio visual media. As for the data collection method using observation and test methods. Data analysis uses qualitative analysis where the author describes the symptoms that occur in the object of research consisting of 22 class V students. This research was conducted in three stages, namely cycle I, cycle II, and cycle III. In the knowledge aspect, the average scores in cycle I, cycle II and cycle III were 71.91; 85.45; and 92.72 respectively. The increase in learning from cycle I to cycle II was 13.54 points, while from cycle II to cycle III was 7.27 points. Meanwhile, in the skill aspect, the average scores in cycle I, cycle II, and cycle III were 66.82; 81.91; and 87.05, respectively. The increase in learning from cycle I to cycle II was 15.09 points, while from cycle II to cycle III was 5.14 points. Keywords: Learning Model; Problem Based Learning; Learning Outcomes